2016
DOI: 10.1093/jnci/djv438
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adjuvant Chemotherapy in Colon Cancer With Microsatellite Instability: A Large Multicenter AGEO Study

Abstract: This study supports the use of adjuvant chemotherapy with fluoropyrimidine plus oxaliplatin in stage III dMMR CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 34 publications
4
108
1
6
Order By: Relevance
“…retrospectively collected FFPE samples). Indeed, 22% of patients with MLH1/PMS2-negative mCRC would have been misclassified using widely-used algorithms combining MMR immunohistochemistry, BRAF mutation, age and Amsterdam II criteria [8,9]. Notably, 38% of sporadic MSI/dMMR mCRCs were BRAF wild-type but MLH1 hypermethylated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…retrospectively collected FFPE samples). Indeed, 22% of patients with MLH1/PMS2-negative mCRC would have been misclassified using widely-used algorithms combining MMR immunohistochemistry, BRAF mutation, age and Amsterdam II criteria [8,9]. Notably, 38% of sporadic MSI/dMMR mCRCs were BRAF wild-type but MLH1 hypermethylated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the addition of oxaliplatine to fluoropyrimidines seems associated with a survival benefit for patients with high-risk stage II or stage III MSI/dMMR CRCs [7,8]. Sensitivity to fluoropyrimidine may differ between sporadic and hereditary stage III MSI/dMMR CRCs [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A DFS benefit from FOLFOX compared with 5-FU alone was observed in a small number of patients with dMMR CRC (Andre et al, 2015). Moreover, a recent study involving 433 dMMR stage-II and stage-III tumours found that adjuvant FOLFOX improved DFS compared to 5-FU alone, with the benefit limited to stage-III tumours and to sporadic cases only (Tougeron et al, 2016).…”
Section: Msi As a Prognostic Marker With Adjuvant 5-fu Plus Oxaliplatmentioning
confidence: 99%